Analysis copy number variation of Chinese children in early‐onset epileptic encephalopathies with unknown cause. Issue 5 (26th April 2016) - Ma, Y.; Chen, C.; Wang, Y.; Wu, L.; He, F.; Chen, C.; Zhang, C.; Deng, X.; Yang, L.; Chen, Y.; Wu, L.; Yin, F.; et al.
Abstract : Abstract : Copy number variations (CNVs) play an important role in the genetic etiology of unknown cause early‐onset epileptic encephalopathies (EOEEs), but the genomic CNVs analysis of Chinese EOEEs children was rare. Here, we identified CNVs by single nucleotide polymorphism array in 116 patients with different subtypes of EOEEs. Of 116 patients 17 (14.66%) carried 19 large CNVs. A total of 14 CNVs in 12 patients were further validated: four of the CNVs were classified as de novo, seven were maternal, and three were paternal. Follow‐up of those 12 patients showed that 5 had been seizure‐free for at least 9 months, 5 had seizures several times per month or per year, and 2 had seizures everyday. But eight patients have profound developmental delay. In this study, we found at least 3.4% of patients had pathogenic CNVs. For the patients, our study laid the foundation for prenatal interventions for their families. Further, we identified potential candidate gene involved in EOEEs. The association of CNVs and clinical features will contribute to the understanding of EOEEs.